POLA ASUH ANAK DALAM SERAT PALIATMA - Nurhidayati Nurhidayati (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2005)
This research study is intended to describe child-rearing patterns in Serat Paliatmaby KGPAA Mangkunagara IV.The source of the data was Serat Paliatma, consisting 18 stanzas in pupuhDhandhanggula (the Dhandhanggula song). The data were collected by meansof orthographic transliteration, translation, paraphrase, and careful readingand rereading. The data were analyzed descriptively. The data validity wasassessed through semantic validity. The data reliability was assessed throughreproducibility.The research findings show that there are two child-rearing patterns in SeratPaliatma, namely (1) the one related to religious norms, and (2) the one related tovalues in life. The former includes acceptance to what is given, gratefulness, anddevotion. Meanwhile, the latter covers asceticism, affection, unity, obedience, loyaltyto the country, and responsibility.Key words: child-rearing pattern, serat, pupuh